Water, Tourism, and Social Change: A Discussion of Environmental Perceptions in Bali - Thomas Wright (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
Water plays an important role in Balinese society. Not only is it commonly featured in Balinese Hindu rituals, but its use and management also enables prosperity through rice cultivation. While these aspects of water have been discussed in many academic and non-academic publications, qualitative understandings of relations to seawater remain somewhat unexplored in the literature. The aim of this paper is to present a preliminary review of existing literature on water and marine environments in Bali, and argue the need for further qualitative social scientific understanding of contemporary Balinese relations to seawater. A discussion of existing research on ocean-centred communities and continued tourism development in Bali’s coastal areas is intended to add to current research in Balinese studies. By presenting literature on Balinese concepts of environment, water and the ocean, this paper seeks to highlight the benefits of continued research on perceptions of environment to discussions of pollution, water scarcity and resource management. Although maritime attractions such as the temples at Tanah Lot and Uluwatu as well as several popular beach communities play a significant role in the tourism industry, this paper suggests the need to further investigate the importance of these attractions to tourists and Balinese as well as the social interpretations associated with them.